Geothermal geology and comprehensive temperature model based on surface and borehole geology in Sengan, Northeast Japan. (November 2022) - Akatsuka, Takashi; Saito, Ryoichi; Kajiwara, Tatsuya; Osada, Kazuyoshi; Nagaso, Masaya; Watanabe, Norihiro; Tsuchiya, Noriyoshi; Asanuma, Hiroshi; Kanetsuki, Takurou
Highlights: Acidic alteration and high-temperature hot springs surround several Quaternary volcanoes within the Sengan area. Quaternary intrusive granitic-dioritic rocks are distributed beneath the Sengan area. Sengan area subsurface temperature was estimated based on temperature logging data. Several high-temperature zones are scattered above sea level in the Sengan area. The granitic-dioritic magma contributes to the formation of geothermal systems in the Sengan area. Abstract: Geological data were used to explore the geological structure and hydrothermal alteration distribution of the Sengan area, Northeast Japan. Acidic alteration and high-temperature hot springs surround several Quaternary volcanoes within the Sengan area. Quaternary intrusive granitic-dioritic rocks are distributed beneath the Kakkonda, Matsukawa, and Matsuo-Hachimantai geothermal fields. In particular, the Kakkonda granite, a heat source in the Kakkonda geothermal field, has a high temperature exceeding 500 °C inside the body. The temperature structure of the Sengan area was investigated using temperature logging data (WD-1a and 53 wells) collected as part of the temperature recovery test conducted in the geothermal wells. The temperature structure was estimated based on temperature extrapolation, a 2-D temperature distribution created with the thin-plate spline method, and a 3-D temperature distribution obtained by combining the horizontal 2-D temperature data. High-temperature zones above 200 °C are distributed at sea level in Nyuto (eastern Lake Tazawa), Kakkonda, Matsukawa, Matsuo-Hachimantai (Hachimantai), and Mt. Akita-Yakeyama, as predicted using the temperature structure estimation method. The granitic-dioritic magma penetrates the pre-Tertiary basement units and the Neogene beneath several fields to form a high-temperature zone in the shallow depth, contributing to the formation of geothermal systems in the Sengan area. However, the linear extrapolation of the subsurface temperature tended to over-estimate the temperature in the greater depth and was valid only at a depth shallower than 3 or 4 km below sea level. This study delineated several high-temperature zones exceeding 200 °C above sea level in the Sengan area.